The two Koreas a contemporary history - Oberdorfer, Don; Carlin, Robert 1947- (New York Basic Books, A member of the Perseus Books Group, 2014)
"Ever since Korea was first divided at the end of World War II, the tension between its northern and southern halves has riveted-and threatened to embroil-the rest of the world. In this landmark history, now thoroughly revised and updated in conjunction with Korea expert Robert Carlin, veteran journalist Don Oberdorfer grippingly describes how a historically homogenous people became locked in a perpetual struggle for supremacy-and how they might yet be reconciled"--
"A new edition of the definitive overview of contemporary Korean history, updated with new material to account for recent, dramatic events"--
Incluye referencias bibliográficas (páginas 473-504)
Keywords: HISTORY / Modern / 20th Century; Korea (South) -- History; Korea (North) -- History; Asia -- Historia